Dual Functional Modification of Alkaline Amino Acids Induces the Self‐Assembly of Cylinder‐Like Tobacco Mosaic Virus Coat Proteins into Gear‐Like Architectures. Issue 10 (1st February 2019) - Zhang, Jian‐Ting; Kankala, Ranjith Kumar; Zhou, Yi‐Hao; Dong, Jin‐Chen; Chen, Ai‐Zheng; Wang, Qiangbin
Abstract: Herein, the assembly of 3D uniform gear‐like architectures is demonstrated with a tobacco mosaic virus (TMV) disk as a building block. In this context, the intrinsic behavior of the TMV disk that promotes its assembly into nanotubes is altered by a synergistic effect of dual functional modifications at the 53rd arginine mutation and the introduction of lysine groups in the periphery at 1st and 158th positions of the TMV disk, which results in the formation of 3D gear‐like superstructures. Therein, the 53rd arginine moiety significantly strengthens the linkage between TMV disks in the alkaline environment through hydrogen bond interactions. The charge of lysine‐modified lateral surfaces is partially neutralized in the alkaline solution, which induces the TMV disk to form a gear‐like architecture to maintain its structural stability by exploiting the electrostatic repulsion between neighboring TMV disks. This study not only provides explicit evidence regarding the molecular‐level understanding of how the modification of site‐specific amino acid affects the assembly of resultant superstructures but also encourages the fabrication of functional protein‐based nanoarchitectures. Abstract : A dual functional modification, including 53rd site arginine mutation and the introduction of lysine groups at the lateral surface, deviates the innate assembly behavior of tobacco mosaic virus coat protein (TMVCP), preferring the formation of a gear‐like superstructure. This study provides a molecular‐level understanding of how the function‐specific amino acid interaction affects the assembly of virus capsid.